Can Growth Opportunity Moderate the Impact of Debt Covenant and Capital Intensity on Accounting Conservatism - Wenten, I ketut; Sakdiyah, Siti Anis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
Accounting conservatism is an important principle in financial reporting because it improves the reliability of financial information and reduces information asymmetry. This study aims to examine the influence of debt covenant and capital intensity on accounting conservatism with growth opportunity as a moderation variable. The study was conducted on non-cyclical consumer companies listed on the Indonesia Stock Exchange for the period 2020–2024 using an associative quantitative approach. The study sample consisted of 39 companies with 195 observations selected through purposive sampling. The data were analyzed using panel data regression with the Fixed Effect Model (FEM). The results showed that debt covenants did not have a significant effect on accounting conservatism, while capital intensity had a significant effect on accounting conservatism. In addition, growth opportunities are not able to moderate the relationship between debt covenants, capital intensity, and accounting conservatism. These findings indicate that capital intensity is a more relevant factor in determining accounting conservatism, while growth opportunity does not strengthen the influence of these two variables.